Effect of menopausal hormone therapy on the skin as a component of healthy aging - S. V. Yureneva; L. M. Ilyina (Медицинский совет, 2018)
Healthy aging (anti-aging) involves the prevention of illness and disability, keeping mental and physical activity in tip-top shape, maintaining the meaning and purpose of life. Women refuse to age and want to look younger as long as possible. The skin is the only organ which condition can be assessed visually, a peculiar mirror that reflects age-dependent changes that take place in the human body and the state of health as a whole. All regular age-dependent changes that occur at the cellular level happen in the skin, therefore, it is often used as a convenient model for studying the biological mechanisms of human aging as a whole [1]. An increase in life expectancy and a stable age of menopause has led to the fact that modern women spend more and more years in postmenopausal state. The direct effects of menopause-related sex hormone production slowing down include loss of fertility, vasomotor symptoms, and the long-term ones such as osteoporosis, cardiovascular disease (CVD) and skin aging, which causes marked discomfort, especially for women [2, 3].